Quantitative evaluation of semi-analytical finite element method for modeling Lamb waves in orthotropic plates - Nissabouri, Salah; El Allami, Mhammed; Boutyour, El Hassan (Comptes Rendus. Mécanique, 2020)
A semi-analytical finite element method algorithm was established to plot the dispersion curves of isotropic aluminum and orthotropic plates. The curves obtained are compared with those plotted by the DISPERSE software and with previous experimental work. The results showed that the accuracy of the method depends on the number of elements for meshing. To ensure good precision and speed of the method, the number of elements per plate thickness must be optimized.